SART3 associates with a post-splicing complex - Klimešová, Klára; Petržílková, Hana; Bařinka, Cyril; Staněk, David (Journal of cell science, 2023)
SART3 is a multifunctional protein that acts in several steps of gene expression, including assembly and recycling of the spliceosomal U4/U6 small nuclear ribonucleoprotein particle (snRNP). In this work, we provide evidence that SART3 associates via its N-terminal HAT domain with the 12S U2 snRNP. Further analysis showed that SART3 associates with the post-splicing complex containing U2 and U5 snRNP components. In addition, we observed an interaction between SART3 and the RNA helicase DHX15, which disassembles post-splicing complexes. Based on our data, we propose a model that SART3 associates via its N-terminal HAT domain with the post-splicing complex, where it interacts with U6 snRNA to protect it and to initiate U6 snRNA recycling before a next round of splicing.
Keywords: malý jaderný ribonukleoprotein U5; Spliceosomes; Splicing; sestřih RNA; spliceozomy; malý jaderný ribonukleoprotein U4-U6; malý jaderný ribonukleoprotein U2; RNA Splicing; Ribonucleoprotein, U2 Small Nuclear; U2 snRNP; U6 snRNA; ribonukleoproteiny malé jaderné; Recycling; Ribonucleoprotein, U5 Small Nuclear; RNA malá jaderná; Ribonucleoprotein, U4-U6 Small Nuclear; RNA, Small Nuclear; Ribonucleoproteins, Small Nuclear